(untitled) (INTERNATIONAL SCIENCE REVIEWS. SOCIAL SCIENCES SERIES, 2024)
The article discusses the question of the form of the exercise of democracy in Russia. Particular attention is devoted to the need to reform the legislation on public hearings.The author touches upon the issues of the significance of this institution, identifies key problems and proposes a set of interrelated measures to improve the institution of public hearings. The urgency of this problem is dictated by the growing importance of the institution of public hearings in Russia.